Plato or Moses?: The Use of the Antiquity Argument in Hellenistic Jewish Writings - Nyström, David E. (Scandinavian journal of the Old Testament, 2024)
In antiquity, apologetic defences often included appeals to an ancient past. Fundamental to the ancient mind was a notion that favoured primitive wisdom over contemporary culture, antiquity over novel discoveries. In the ongoing clashes between cultures and ethnicities which signified the Hellenistic era, this notion was often combined with a competitive search for communal recognition and validity. This article offers a survey of Jewish authors in Hellenistic times, who engaged in this battle for old age. The article shows how various Jewish writers employed the antiquity argument through comparative historiography, in which they traced the roots of civilization to ancient heroes of Israel. The article ends with a discussion on the logic, structure, and purpose of the antiquity argument.